The Effect of Digital Wordwall-Based Learning Media to Improve Early Childhood Numeracy Skills - Muhammad Yusri Bachtiar; Hasmawati; Parwoto; Tri Sugiarti; Andi Nur Maharani; Jumriani Sultan; Gulzhaina K.Kassymova (Universitas Pendidikan Ganesha, 2025)
Early childhood often experiences obstacles in understanding the concept of early numeracy, so learning media that is able to support their cognitive development optimally is needed. This study aims to analyze the effectiveness of Wordwall digital learning media in improving children's early numeracy skills. The method used is quantitative with a pseudo-experimental design using the Paired Sample T-Test. The subjects consisted of 20 children aged 5–6 years. Data collection through observation and initial numeracy tests. The instrument was expertly validated using Aiken's V analysis and tested for reliability with Alpha Cronbach with validation results showing that all instrument items were valid. Data normality and homogeneity tests are eligible for parametric analysis. The results of the Paired Sample T-Test showed that there was a significant influence of the use of Wordwall media on improving children's early numeracy skills. The results of this study show that Wordwall learning media is feasible and effective in numeracy learning in early childhood. This study recommends Wordwall as an alternative interactive digital media that can increase learning motivation and make it easier for teachers to design fun and meaningful learning.